2010
DOI: 10.1038/aps.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical heart function by trimetazidine in db/db mice

Abstract: Aim: To investigate the influence of trimetazidine, which is known to be an antioxidant and modulator of metabolism, on cardiac function and the development of diabetic cardiomyopathy in db/db mouse. Methods: Trimetazidine was administered to db/db mice for eight weeks. Cardiac function was measured by inserting a Millar catheter into the left ventricle, and oxidative stress and AMP-activated protein kinase (AMPK) activity in the myocardium were evaluated. Results: Untreated db/db mice exhibited a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 57 publications
2
18
2
1
Order By: Relevance
“…Trimetazidine works by inhibiting the LC 3-KAT enzyme of the β-oxidation pathway (Kantor, et al, 2000), but also has weak inhibitory effects on CPT1 (Lee, et al, 2004). An experimental study in mice with diabetic cardiomyopathy demonstrated improvements in both systolic and diastolic function following trimetazidine treatment, as well as a reduction in ROS and improvement in cardiac energetic status (Li, et al, 2010). Clinical studies in man have also supported the beneficial effects of trimetazidine.…”
Section: Partial Fatty Acid Oxidation Inhibitionmentioning
confidence: 95%
“…Trimetazidine works by inhibiting the LC 3-KAT enzyme of the β-oxidation pathway (Kantor, et al, 2000), but also has weak inhibitory effects on CPT1 (Lee, et al, 2004). An experimental study in mice with diabetic cardiomyopathy demonstrated improvements in both systolic and diastolic function following trimetazidine treatment, as well as a reduction in ROS and improvement in cardiac energetic status (Li, et al, 2010). Clinical studies in man have also supported the beneficial effects of trimetazidine.…”
Section: Partial Fatty Acid Oxidation Inhibitionmentioning
confidence: 95%
“…This effect of adiponectin likely increases complete oxidation of fatty acids and limits the likelihood that toxic lipid intermediates will accumulate. Trimetazidine, an inhibitor of long-chain 3-ketoacyl coenzyme A thiolase activates AMPK, reduces lipid accumulation, and restores contractile function in db/db diabetic mice [64]. The mechanism of action of trimetazidine also involves amelioration of oxidative stress via increased antioxidant defenses, such as MnSOD.…”
Section: Part 2 Lipotoxicity and Cardiac Functionmentioning
confidence: 99%
“…Moreover, the use of high TMZ doses leads to the maintenance of electrolyte homeostasis in myocardium by protecting the cardiac cells from the accumulation of calcium and sodium ions in ischemic hearts . It is also known that long‐term treatment with TMZ alleviates the myocardial accumulation of the oxidation reactive form and prevents lipid per‐oxidation . It improves the activity of the superoxide dismutase (an antioxidant enzyme) and relieves the oxidative stress phenomena .…”
Section: Introductionmentioning
confidence: 99%